The use of formal and informal curative services in the management of paediatric fevers in four districts in Kenya. - Amin, A; Marsh, V; Noor, A; Ochola, SA; Snow, R (2003)
OBJECTIVE: To assess the sources, costs, timing and types of treatment for fevers among children under 5 years of age in four ecologically distinct districts of Kenya. METHODS: Structured questionnaires were administered to caretakers of one randomly selected child aged <5 years per homestead to establish whether the child had had a fever within the last 14 days and the types, sources, costs, and timing of treatment. Drug charts of common proprietary anti-malarial and antipyretic drugs in Kenya were used as visual aids. RESULTS: A total of 2655 fevers were reported among 6287 (42.2%) children with significant differences between the four districts (P<0.01). A substantial number of fevers remained untreated (28.1%) across all districts and more fevers were treated in Greater Kisii than any other district (P<0.01). The median delay to any treatment was 2 days [inter-quartile range (IQR): 2, 4]. The informal retail sector had no transport costs associated with it and charged less for drugs than all the other sectors. Most antimalarial treated fevers occurred in the formal public sector (52.6%). Only 2.3% of fevers were treated within 24 h of onset with a sulphur-pyrimethamine drug, the nationally recommended first-line drug for the management of uncomplicated malaria. CONCLUSIONS: The Abuja target of ensuring that 60% of childhood fevers are treated with appropriate antimalarial drugs within 24 h of onset by 2010 is largely unmet and a major investment in improving prompt access to antimalarial drugs will be required to achieve this.